P42 Associations of cognition in adolescence and midlife with bone health in later life: Results from the MRC National Survey of Health and Development. (13th September 2016) - Bendayan, R; Muthuri, S; Muniz, G; Cooper, R; Adams, J; Cooper, C; Richards, M; Kuh, D
Abstract : Background: Fractures are associated with mortality and disability and low bone mineral density (BMD) is a known predictor of fracture risk. Research has found an association between cognitive impairment and increased risk of fracture and one possible mechanism is via low BMD. Existing studies have examined BMD as a predictor of cognitive performance. However, it has been suggested that this association might operate in the reverse direction. The MRC National Survey of Health and Development provides a unique opportunity to investigate the associations of cognitive function in adolescence and midlife with bone health at age 60–64. Methods: The sample consisted of 658 men and 697 women with pQCT derived measures of trabecular, cortical and total vBMD, distal cross-sectional area (CSA), CSA of the diaphysis and the medullary cavity (medullary CSA), and polar strength strain index (SSI). Cognitive performance was measured using an overall score of general cognitive ability at age 15, and memory and reading ability tasks at age 53. A series of hierarchical multiple regression analyses were performed for each pQCT measure which were adjusted for body size, smoking and socio-economic position. Results: For men, when cognition at age 15 and 53 were independently entered in unadjusted and body size adjusted models, both were found to be negatively associated with diaphysis, medullary and distal CSA and SSI, and positively associated with cortical, trabecular and total vBMD. When cognition at age 15 and 53 were mutually adjusted, only cognition at age 15 remained associated with most of the bone outcomes. For example, after adjusting for body size and cognition at 53, 1 point increase in cognition at age 15 was associated with a 4.3% (95% CI −8.3%, −0.3%; p = 0.03) lower Medullary CSA and a 3.8% (95% CI 1.1%, 6.5%; p = 0.006) greater trabecular vBMD. For women, although there was some evidence of associations in unadjusted models, these were fully attenuated once body size was adjusted for. Discussion: The associations of cognition in adolescence and midlife with bone health at 60–64 are different for men and women. For men, lower cognitive performance at age 15 and 53 is associated with greater bone size and strength and less bone density at 60–64. For women, it appears that other variables may have a key role in this association. Cognitive performance in early life is associated with bone health in later life and further studies should explore the different underlying mechanisms for men and women.